Was Drug Proving made on Healthy or Relatively Healthy or Miasmatic one; Men and Women by Dr. Hahnemann & his disciples before 1816 to 1828.? or/ and after 1816 on Miasmatic Personals? (Advancements in Homeopathic Research, 2022)
Wherever humans go they found calamities, diseases and deaths. People were buried under sand, mud, mountains, etc., they (scientists) found skeletons after excavation. What was/were the cause/causes? Some said that it is due to plague, or some kind of epidemics, malaria, cancer, etc.; but nobody knows what is/are the exact cause or causes. If we find the causes we can prevent or treat people with some plants or minerals as medicines. Question is what type of medicine? How to know that a certain plant or mineral will cure or is poison to man? How to give them? Was there any method, rule or Law? No. Let us take the history of medicine. Actually nobody knows the history. Let us take first century. During olden days for various diseases, plants, leaves, juices, barks, minerals, etc; were used singly or in mixtures of many so called medicines/drugs and experiments were done on patients. There was no method, rule or law. All was in chaos and thousands were disfigured, suffered, poisoned, burned, dead and buried. Now let us take from 15th. Century and forget the past. Should we?
Keywords: calamities; epidemics; malaria; cancer; drugs/medicines